EFEKTIVITAS SISTEM HUKUM PIDANA DALAM PENANGANAN NARKOTIKA DI INDONESIA - Aldi Pradani; Abdurrakhman Alhakim; Ampuan Situmeang (Jurnal Hukum to-ra : Hukum untuk mengatur dan melindungi masyarakat, 2026)
The issue of narcotics in Indonesia has reached a critical point, marked by the high rate of distribution and abuse , which significantly affects social stability and the younger generation. Although Indonesia has enacted strict regulations through Law Number 35 of 2009 on Narcotics,the effectiviness of the criminal justice system in addressing narcotics related crimes remains in question. This study aims to analyze the effectiveness of the criminal justice system in handling narcotics offenses,with a focus on the system itself and the recurring phenomenon of user relapse. The research adopt a normative juridicial approach. The findings indicate a persistent gap between legal norms and their implementation,particularly in law enforcement,rehabilitation processes,and inter agency cordination. The high relapse rate suggests that repressive legal approaches have not addressed the root causes of the problem. There is a need to strengthen legal subtance,legal culture,the integrity of law enforcement officers,and to optimize rehabilitative and restorative approaches in handling narcotics abuse. An ideal criminal justice system should not only punish but also rehabilitate,provide justice, and ensure comprehensive protection for society